The Importance Of The Karakalpak Language And The Use Of Some Words Inaccurately - Gulkhan Nurlibekova (International Scientific and Current Research Conferences, 2021)
This article discusses the importance of the Karakalpak language and its proper use, the importance of written literacy, the lack of attention to correct writing among young people, even adults, social evidenced by examples in networks and ads.